2006
DOI: 10.1038/modpathol.3800626
|View full text |Cite
|
Sign up to set email alerts
|

Novel identification of zyxin upregulations in the motile phenotype of hepatocellular carcinoma

Abstract: Genome-wide copy number aberrations are common in hepatocellular carcinoma, although the precise genetic events underlying disease progression remain poorly defined. Previous work from our group has indicated several regional chromosomal gains such as chromosome 7q34-q36 that are associated with advanced metastatic tumors. Although the distal chromosome 7q gains have also been implicated in the progression of other malignancies, information on underlying targeted genes is limited. In this study, we have examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…The differential effects of perturbed zyxin function on EMT in two model systems likely highlights distinct roles for zyxin at different cellular sites, namely focal adhesions/stress fibers and cell-cell adhesions. In fact, this may also explain why cancer progression has been associated with both increased and decreased zyxin expression in different model systems (van der Gaag et al, 2002;Amsellem et al, 2005;Sy et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…The differential effects of perturbed zyxin function on EMT in two model systems likely highlights distinct roles for zyxin at different cellular sites, namely focal adhesions/stress fibers and cell-cell adhesions. In fact, this may also explain why cancer progression has been associated with both increased and decreased zyxin expression in different model systems (van der Gaag et al, 2002;Amsellem et al, 2005;Sy et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Upregulation of zyxin in HCC tumors had been previously observed by quantitative reverse transcription-polymerase chain re- action [42]. Zyxin is a focal-adhesion-associated phosphoprotein with an apparent molecular weight of 82-84 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies showed that overexpression of PXN, TLN1, ZYX or PIK3R2 increases cell migration and/or metastasis in various cancer types including PCa. 5, 6, 7, 8 …”
Section: Introductionmentioning
confidence: 99%